Gastrointestinal stromal tumor – case report - Sousa, Elisabete; Araújo, Rosário; Garcia, Juan; Rua, Abel (Portuguese Journal Internal Medicine, 2007)
The authors present a clinical case report, of a 73 year-old female patient, with hypochromic, microcytic anaemia and serum iron deficiency, of two years duration. The out-patient colonoscopic and upper gastro-duodenal endoscopic studies were inconclusive. She presented with a decline in general status, asthenia and anorexia of two months duration, as well as dark stools and tachycardia, four days before hospitalization. Physical examination revealed pallor of skin and mucosae and vital signs were stable. Analyses showed a normochromic, normocytic anaemia (5.7 g/dl), without signs of haemolysis, serum iron =7 ug/dl, transferrin saturation= 24.5 %, reticulocytes = 6%, RDW increased; normal levels of serum electrolytes, normal renal and thyroid function tests; negative tumour markers and increased ESR (124 mm/h). Stool occult blood was positive in three samples. A repeat upper gastro-duodenal endoscopy and colonoscopy were negative. Barium radiographic studies did not show images suggestive of tumour or infiltrative injury. Abdominal and pelvic ultrasound showed an image compatible with an intra-abdominal heterogeneous mass. CT scan revealed a mass in the right lower abdominal, probably an ileal lesion, with 6 cm of longitudinal diameter suggestive of a tumour; a small amount of ascites but without evidence of lymph node involvement in the main abdominal and pelvic chains. She underwent a segmental enterectomy and appendicectomy. Histological examination showed malignant Gastrointestinal Stromal Tumour (GIST) with signs of muscular differentiation, positive C-Kit. At present, after two years of follow-up, the patient remains asymptomatic.